Genetic Relationships Analysis of Some various Species Using Cytochrome b Genes as a Phylogenetic Marker - Lajan Salahaldin Ahmed (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study examined the genetic relationships among six species—chicken (Gallus gallus), quail (Coturnix coturnix), duck (Anas platyrhynchos), goose (Anseranser domestica), and turkey (Meleagris gallopavo) and rabbit (Lepus capensis), using partial mitochondrial cytochrome b (Cyt-b) gene sequences. PCR amplification of the mitochondrial Cyt-b gene resulted in an approximately 358 bp amplicon in size for all species, and sequences alignment and phylogenetic analyses were performed with Bio Edit and MEGA X software’s to determine genetic similarities and distances. Results revealed high nucleotide similarity between chicken and quail (89.1%) and chicken and turkey (83.6%). The closest genetic relationship was between duck and domestic goose, with 87.4% identity and the smallest genetic distance of 0.126. Chicken (Gallus gallus) demonstrated a relatively close relationship with both duck and domestic goose, with identities (83.6%). While, Turkey (Meleagris gallopavo) exhibited a slightly more distant relationship with avian species, with the lowest similarity at 81.6% with domestic goose. The rabbit, positioned at the root of the phylogenetic tree, exhibited the greatest genetic distance from avian species, with a 28.3% distance and 71.7% identity with chicken. This study provides solid evidence of the effectiveness of using Cyt-b gene sequences as a reliable tool for species identification across various applications, underscoring the effectiveness of partial Cyt-b gene sequences for avian species identification and genetic analysis, which is valuable for breeding and diversity studies.